Pembinaan Keagamaan: Urgensi dan Dampaknya Terhadap Religiusitas dan Etos Kerja Civitas Akademika IAIN Sorong - Sari, Fatma; Hartinah, Hartinah (Al-Riwayah : Jurnal Kependidikan, 2023)
The purpose of this study was to investigate the urgency of religious coaching for the IAIN Sorong academic community, to explore the impact of religious coaching on the religiosity of the academic community of IAIN Sorong, and to explore the impact of religious coaching on the work ethic of the Sorong IAIN academic community. The type of research used in this research was qualitative research. Qualitative research focuses on natural phenomena or events. The research subjects were the academic community of IAIN Sorong, West Papua. The research procedure used in this study was to collect data in the form of observations, interviews and documentation. In this study, the data analysis used consisted of 3 stages, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that religious coaching is important for the academic community of IAIN Sorong and for the community because it has an effect or implication for the continuation and continuity of the enthusiasm and performance of lecturers and staff at IAIN Sorong. The impact of religious coaching on the religiosity of the academic community at IAIN Sorong is quite significant. Religious coaching can add spiritual insight to the IAIN Sorong academic community which can be applied in carrying out work. The impact of religious coaching on the work ethic of the academic community at IAIN Sorong includes motivation, responsibility and quality of performance. Keywords: Religious Coaching, Religiosity, Work Ethic, Academic Community